Behind chocolate bars - Aarons, Kathy (Aarons, Kathy. Chocolate covered mystery., 2016)
Best friends and business partners Michelle and Erica have a monstrous to-do list as they prepare for the annual West Riverdale Halloween Festival. Their shop, Chocolates and Chapters, will have a booth at the event, where Michelle will serve spooky delights while Erica displays an assortment of spine-chilling books. Thank goodness the teenagers from Erica's comic-book club are chipping in to help. But one of their volunteers winds up in trouble after a woman's body is found in an abandoned house--with the teen's superhero key ring close by.